STRATEGI PEMBELAJARAN AKIDAH DALAM PENDIDIKAN AGAMA ISLAM: STUDI KUALITATIF BERBASIS WAWANCARA GURU PAI DI MTS NURUL AMAL - Ari Indri Yani; Eka Nursaadah; Enan Kusnandar (CV. Kalimasada Group, 2026)
Aqidah learning plays a strategic role in shaping students’ faith, attitudes, and religious character. This study aims to analyze the strategies of aqidah learning implemented by Islamic Religious Education (PAI) teachers, including teachers’ understanding, learning strategies and methods, the use of learning media, learning evaluation, as well as supporting and inhibiting factors. This research employs a qualitative approach with a descriptive method through interviews with PAI teachers. The findings indicate that aqidah learning strategies are implemented through differentiated instruction by applying lecture, discussion, question-and-answer, and exemplary methods, supported by various learning media. The evaluation of learning encompasses cognitive, attitudinal, and behavioral aspects. A religious school environment serves as the main supporting factor, while environmental influences and excessive use of social media become the inhibiting factors.